Criticism of the Phenomenological Approach: Understanding the Limits of Subjectivity and Objectivity in Research - Annisa, Silvia (Talenta Publisher, 2024)
Along with criticism of objectivity, phenomenology is also often criticized for limitations in the generalization of findings. Because of its focus on unique individual experiences, phenomenology tends to ignore the social, cultural, and historical contexts that may influence those experiences. This makes it difficult to generalize phenomenological findings to wider populations, and limits their relevance in more general theory development. Along with criticism of objectivity, phenomenology is also often criticized for limitations in the generalization of findings. Because of its focus on unique individual experiences, phenomenology tends to ignore the social, cultural, and historical contexts that may influence those experiences. This makes it difficult to generalize phenomenological findings to wider populations, and limits their relevance in more general theory development. This article uses the literature study method to explore research objectives, using articles, books and other reference sources.